Customer Reliationship Pada PT Muliaglass Float Division 3 - Thoriq Baihaqi Al Syukri; Puji Isyanto; Dini Yani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to carry out Customer relationship marketing or CRM activities at PT. MuliaGlass is a form of service quality that is measured through commitment, communication, and complaint handling. Customer trust and loyalty are expected to increase by managing these three dimensions. This method uses a qualitative method, namely by making observations in the scope of the company, paying attention to how the processes occur within the company, paying attention to the preparation of the administration of shipping and receiving goods in the company, observing the process of complaints submitted by customers to the company. Then the results of this study indicate that the commitment and complaint handling of PT. MuliaGlass has a positive influence on customer trust. However, this Practical Work shows that communication has no effect on customer trust.